Evaluasi Kebijakan Pelayanan BPJSKesehatan di Ruang VIP Edelweiss Rumah Sakit Umum Daerah (RSUD) dr. M. M. Dunda Limboto Kabupaten Gorontalo - Fatrawin Kai; Rifka S. Akibu; Widya Kurniati Mohi; Muh. Firyal Akbar (Jurnal Media Administrasi, 2025)
This study aims to determine and evaluate the BPJS Health Service Policy in the VIP Room of Edelweiss, Dr. M. M. Dunda Limboto Regional General Hospital, Gorontalo Regency. The research method used is qualitative descriptive. The results of the study indicate that several indicators of the effectiveness of the BPJS Health service policy in the VIP Room of Edelweiss, Dr. M. M. Dunda Limboto Regional General Hospital have not been running optimally. In terms of effectiveness, the administrative procedures are still considered unclear and not easy by patients and families, especially with the time limit for processing BPJS only 3 x 24 hours. The adequacy indicator is running quite well, but administrative information is only delivered verbally without written support, so patients or their families often have to ask again for the information needed. In terms of equality, although there are differences in facilities and comfort between the VIP room and the general care room, equality in processing BPJS administration is maintained. Responsiveness is considered good; administrative officers are considered fast and precise in providing solutions to obstacles faced by patients. However, in the accuracy indicator, some informants felt that the time given for administrative management was not yet in accordance with needs, especially for patient families who live far away or have other activities. This indicates the need for a re-evaluation of the time provisions and the delivery of more complete and written information.